1984
DOI: 10.1063/1.447914
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory detection of the 11←111 submillimeter wave transition of the H2D+ ion

Abstract: The 110←111 transition of H2D+ was detected in a dc discharge in Ar–H2–D2 mixtures with liquid nitrogen cooling and an applied axial magnetic field. The transition frequency was determined to be 372 421.380±0.100 MHz. This transition is expected to be the most favorable one for radioastronomical detection of this very crucial ion in the interstellar medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…The line center was measured by fitting observed line profiles to the Gaussian line profile, assuming that pressure broadening was negligible. The frequency for the H 2 D + line determined here was found to be close to the one measured by Warner et al [15], but the new measurement should be more accurate. The frequency for the 1 10 À 1 01 transition of D 2 H + turned out to be higher by 43 kHz than our own previous value.…”
Section: Spectroscopy Of H 2 D + and D 2 H +supporting
confidence: 65%
See 4 more Smart Citations
“…The line center was measured by fitting observed line profiles to the Gaussian line profile, assuming that pressure broadening was negligible. The frequency for the H 2 D + line determined here was found to be close to the one measured by Warner et al [15], but the new measurement should be more accurate. The frequency for the 1 10 À 1 01 transition of D 2 H + turned out to be higher by 43 kHz than our own previous value.…”
Section: Spectroscopy Of H 2 D + and D 2 H +supporting
confidence: 65%
“…Vastel et al [17] derived the v LSR for H 2 D + and D 2 H + to be 3.55 ± 0.02 and 3.76 ± 0.03 km/s, respectively, by using the laboratory frequencies [14,15,20]. They suggested that the difference of the v LSR for these two species might have been caused by possible systematic deviations, albeit small, of the laboratory measurements.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations